Difficulties with being socially accepted: An experimental study in borderline personality disorder - Liebke, Lisa; Koppe, Georgia; Bungert, Melanie; Thome, Janine; Hauschild, Sophie; Defiebre, Nadine; Izurieta Hidalgo, Natalie A.; Schmahl, Christian; Bohus, Martin; Lis, Stefanie (Journal of abnormal psychology, 2018)
Anxious preoccupation with real or imagined abandonment is a key feature of borderline personality disorder (BPD). Recent experimental research suggests that patients with BPD do not simply show emotional overreactivity to rejection. Instead, they experience reduced connectedness with others in situations of social inclusion. Resulting consequences of these features on social behavior are not investigated yet. The aim of the present study was to investigate the differential impact of social acceptance and rejection on social expectations and subsequent social behavior in BPD. To this end, we developed the Mannheim Virtual Group Interaction Paradigm in which participants interacted with a group of computer-controlled avatars. They were led to believe that these represented real human coplayers. During these interactions, participants introduced themselves, evaluated their coplayers, assessed their social expectations and received feedback signaling either acceptance or rejection by the alleged other participants. Subsequently, participants played a modified trust game, which measured cooperative and aggressive behavior. Fifty-six nonmedicated BPD patients and 56 healthy control participants were randomly and double-blindly assigned to either the group-acceptance or group-rejection condition. BPD patients showed lower initial expectations of being socially accepted than healthy controls. After repeated presentation of social feedback, they adjusted their expectations in response to negative, but not to positive feedback. After the experience of social acceptance, BPD patients behaved less cooperatively. These experimental findings point to a clinically relevant issue in BPD: Altered cognitive and behavioral responses to social acceptance may hamper the forming of stable cooperative relationships and negatively affect future interpersonal relationships. (PsycINFO Database Record (c) 2018 APA, all rights reserved)
Gesehen am 20.02.2020